LEGAL BASIS FOR THE IMPLEMENTATION OF STATE POLICY IN THE FIELD OF AIR TRANSPORT - Polishchuk, Inna; Kononenko, Dmytro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to study the issues of the current state of legal regulation of the implementation and enforcement of the state policy in the field of air transport at the national and global levels. Methods: the study was conducted using general scientific and special legal methods: cognition, theoretical analysis, synthesis, comparison, systematization, generalization, etc. Results: the essence of the state policy in the field of air transport as a systemic category is clarified, including the definition of the peculiarities of the content and nature of the constituent elements of its implementation - state regulation, state administration and state control in this area; the forms, methods and subjects that ensure its implementation are determined. It is substantiated that the State policy in the field of air transport is implemented through the regulatory influence of the relevant rules of law, and the effectiveness of its implementation directly depends on the state of its legal regulation, which at the current stage of the state’s development is conditioned by the priorities of ensuring Ukraine’s integration into the common aviation area with the EU, and the implementation of state support measures for the air transport industry of Ukraine. Discussion: the need to improve the efficiency of operation and ensure the safety of air transport in the future, the existence of legislative, economic and organizational problems in this area, further scientific study of the effectiveness of the implementation and improvement of state policy in the field of air transport under martial law and post-war development of the country. One of the priorities of the national state policy in the field of air transport should be to improve the regulatory and legal support for the development of this sector and the air transport services market, to develop mechanisms of public-private partnership, including investment, and, of course, to improve the level and ensure safety. Given the existing challenges of martial law, it is the effectiveness of the implementation of state policy in this area that can ensure the support and development of air transport through the application of a comprehensive package of measures to be implemented through the mechanisms of innovation and investment development of the air transport industry, improving its safety, environmental friendliness, etc. The author emphasizes that only if the above-mentioned goals of the State policy in the field of air transport are implemented at the State level, further development of the air transport industry is possible to meet the needs of the economy and society as a prerequisite for sustainable development of the country, ensuring national security and State sovereignty of Ukraine.